Agronomic performance and silage quality traits of forage sorghum hybrids in 1994 - Mitchem, M.S.; Pfaff, L.; Bolsen, K.K.; Young, Matthew A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
The 1994 growing season was characterized by near norm al rainfall and temperatures. Both whole-plant DM and grain yields were excellent for all hybrid s. The middle-season Pioneer 947 hybrid had the highest grain yield. The two dual-purpose hybrids had the highest whole-plant DM yields, and the male sterile (Golden Harvest H-1) and the grain sorghum (DeKalb 42Y) had the lowest. Strong winds in the first week in September caused substantial lodging in three of the four tall middle- and late-season hybrids (DeKalb FS-5 and Golden Harvest H-2 and H-68). Two of the short height, dual purpose hybrids (Northrup King 300 and Golden Harvest H-45) were not affected. The 10 sorghum hybrids differed significantly in the three important silage quality traits – whole-plant DM, crude protein, and acid detergent fiber.
Keywords: Beef; Forage sorghum; Hybrid; Silage; Yield